Analisis kepuasan pelanggan terhadap kinerja kontraktor pada proyek sistem penyediaan air minum di Kabupaten Minahasa Utara - Suci Cahyani Mukramin; Arthur H. Thambas; Ariestides K. T. Dundu; Grace Y. Malingkas (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Improving the quality of the water supply system in North Minahasa Regency is a priority for community welfare through the provision of clean water that supports health, sanitation, and the economy. Contractor performance plays a key role in project success. However, projects often experience delays or failure, so customer satisfaction is not met. This research aims to measure customer satisfaction with contractor performance and identify features that influence satisfaction to provide recommendations for improving contractor performance. A quantitative approach was used through a survey with questionnaires distributed to project owners, supervisory consultants, and technical teams involved between 2021 and 2024. Data analysis was carried out using the Naïve Bayes algorithm and backward elimination techniques to filter out insignificant features. The results showed that 81.4% of customers were satisfied with the contractor's performance, with the model showing 87.14% accuracy, 94.44% precision, and 89.47% recall. The main features that influence satisfaction are: project work performance domain at the planning process, delivery performance domain at the execution process, delivery performance domain at the monitoring and controlling process, measurement performance domain at the execution process, uncertainty performance domain at the initiating process, uncertainty performance domain at the planning process, and uncertainty performance domain at the monitoring and controlling process. Therefore, the Naïve Bayes algorithm is effective in analyzing customer satisfaction data and providing useful insights for contractors.